2013
DOI: 10.1177/0956797613486989
|View full text |Cite
|
Sign up to set email alerts
|

Do Girls Really Experience More Anxiety in Mathematics?

Abstract: Two studies were conducted to examine gender differences in trait (habitual) versus state (momentary) mathematics anxiety in a sample of students (Study 1: N = 584; Study 2: N = 111). For trait math anxiety, the findings of both studies replicated previous research showing that female students report higher levels of anxiety than do male students. However, no gender differences were observed for state anxiety, as assessed using experience-sampling methods while students took a math test (Study 1) and attended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
257
4
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(312 citation statements)
references
References 28 publications
38
257
4
13
Order By: Relevance
“…For females, the negative path between learning anxiety and self-efficacy was stronger, suggesting that in the case of a male and female student with equally high level of learning anxiety, the female's self-efficacy would be lower. This finding is in line with existing academic emotion research in STEM (Goetz et al 2013) highlighting gender differences in state anxiety and perceptions of competence despite equivalent levels of objective academic performance. One potential explanation may be the aversive effects of gender-based stereotype threats on females' perceptions of how they should think and feel towards STEM-related activities and outcomes (Smith and Hung 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For females, the negative path between learning anxiety and self-efficacy was stronger, suggesting that in the case of a male and female student with equally high level of learning anxiety, the female's self-efficacy would be lower. This finding is in line with existing academic emotion research in STEM (Goetz et al 2013) highlighting gender differences in state anxiety and perceptions of competence despite equivalent levels of objective academic performance. One potential explanation may be the aversive effects of gender-based stereotype threats on females' perceptions of how they should think and feel towards STEM-related activities and outcomes (Smith and Hung 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Thus far, mathematics anxiety has received substantial empirical attention, and it has been found to have negative effects on student persistence and achievement in mathintensive domains (Ashcraft 2002;Ma 1999). Several studies have shown that girls often are more anxious than boys in contexts that involve mathematical reasoning and that domainspecific anxiety has an important influence on the development of gender differences in math performance (Devine et al 2012;Goetz et al 2013). Previous studies have also found relations between mathematics anxiety and mathematics self-efficacy (Hoffman 2010;McMullan et al 2012).…”
Section: Mathematics Anxietymentioning
confidence: 99%
“…User-Adaptive Approaches and User Models What makes these approaches useradaptive is that they are customized to individual learners based on the information collected about them. Specifically, adaptive proactive approaches involve making changes to features of the ALT based on a user model that is informed by information about the student such as gender, culture, personality traits, or prior knowledge that are associated with variations in the frequency and intensity of emotion as well as varying dispositions toward prompts designed to support adaptive emotions and learning Frenzel et al 2007;Goetz et al 2013;Rosiek 2003). …”
Section: Proactive Approachesmentioning
confidence: 99%
“…2). Delivering prompts designed to help girls overcome tendencies to (inaccurately) rate their competency as lower than boys in mathematics (Goetz et al 2013) would constitute a user-adaptive proactive approach, where static demographical information about the learner is used tailor the intervention (i.e., boys and girls might receive a different math message in this case). The final type of emotion regulation in four-fold conception of emotion regulation is emotionoriented regulation (i.e., suppression ;Gross 2015).…”
Section: Integrating Proactive and Reactive Featuresmentioning
confidence: 99%
“…Concerning the trait-state discrepancy in anxiety, previous studies have found that academic self-concept, which is an identity-related subjective belief, influences the extent trait anxiety measures are overestimated in comparison with state anxiety measures (Bieg, Goetz, & Lipnevich, 2014;Goetz, Bieg, Lüdtke, Pekrun, & Hall, 2013). The academic self-concept is a mental representation of the abilities and competencies a person has (Nagengast & Marsh, 2012) and can be defined as an evaluative self-perception that is formed through experience with and interpretation of one's school environment (Marsh & Craven, 1997).…”
Section: Introductionmentioning
confidence: 99%